A Myb transcription factor, PgMyb308-like, enhances the level of shikimate, aromatic amino acids, and lignins, but represses the synthesis of flavonoids and hydrolyzable tannins, in pomegranate (Punica granatum L.). Issue 1 (11th February 2022) - Dhakarey, Rohit; Yaritz, Uri; Tian, Li; Amir, Rachel
Abstract: Pomegranate fruit peels are highly abundant in metabolites derived from the shikimate pathway, such as hydrolyzable tannins (HTs) and flavonoids. These metabolites are beneficial to human health (commercial juice is enriched with peel metabolites), and also protect the fruit from environmental stresses. To understand the transcriptional control of shikimate pathway-related metabolites in pomegranate, we cloned and characterized a subgroup S4 R2R3 Myb transcription factor, Pg Myb308-like. Overexpressing PgMyb308-like in pomegranate hairy roots increased the accumulation of shikimate, aromatic amino acids, isoferulic acid, and total lignins, but led to reduced gallic acid and its downstream products HTs, as well as multiple flavonoids. Changes in these metabolites are supported by the increased expression of 3-deoxy-D-arabino-heptulosonate 7-phosphate synthase and shikimate dehydrogenase 1 ( PgSDH1 ) (the SDH isoform associated with shikimate biosynthesis), and the reduced expression of PgSDH4 (the SDH isoform suggested to produce gallic acid). Transcriptome analysis of PgMyb308-like- overexpressing hairy roots further revealed reprogramming of cell wall-related genes, while overexpression of PgMyb308-like in Arabidopsis thaliana plants uncovered its distinct role in a different genetic and metabolic background. These results together suggest that Pg Myb308-like activates genes in the shikimate pathway and lignin biosynthesis, but suppresses those involved in the production of HTs and flavonoids.